Antimicrobial activity studies of the metal complexes derived from cyclobutane-substitued thiazole carbamate ligands - Çukurovah, A; Yilmaz, L; Ahmedzade, M; Kirbag, S (John Wiley & Sons Inc, 2001)
Two novel monodentate carbamate ligands derived mainly from 4-(1-methyl-1-phenylcyclobutyl-3-yl)-2-aminothiazole and 4-(1-phenyl-1-methylcyclobutane-3-yl)-2-(N-methyl)aminothiazole, have been prepared. The ligands and their metal complexes have been characterized bi, elemental analyses, IR, C-13, and H-1 NMR spectra, as well as UV-Vis, and magnetic susceptibility measurements. Both ligands contain I mole of water of crystallization and all complexes are mononuclear. Antimicrobial activities of the ligands and their complexes have been screened against the Bacillus subtitis IMG 22 (bacteria), Micrococcus luteus LA 2971 (bacteria), Escherichia coli DM (bacteria), Staphylococcus aureus COWAN I (bacteria), Saccharamyces cerevisiae UGA 102 (yeast), and Candida albicans CCM 314 (yeast). Thermal properties of the ligands and their complexes have been studied by thermogravimetric analyses (TGA) and differential scanning calorimetry (DSC). (C) 2001 John Wiley & Sons, Inc.